The effect of educational intervention on the quality of life of acute lymphocytic leukemia who undergoing chemotherapy - Novrianda, Dwi; Khairina, Ilfa (International Journal of Research in Medical Sciences, 2017)
Background: Increased knowledge of the parents about the problems and needs of children has an important effect on family support so that parents can provide optimal care to improve the quality of life of children. The purpose of study was to determine the effect of educational intervention chemotherapy for parents on the quality of life of children acute lymphocytic leukemia. Methods: The study design was a quasi-experimental design with The One Group Pretest-Posttest design. For the first, it was performed measurements the quality of life of children using a questionnaire. Furthermore, giving education for parents for 45 minutes, then measured using the same instrument on the seventh day after the education. This research has been conducted in the Pediatric Inpatient Dr M. Djamil Hospital Padang start from February to November 2014. The sample was taken using consecutive sampling. Based on the hypotheses sample test obtained the minimum number of samples was 24. The instrument used was a quality of life questionnaire developed by J. W. Varni i.e PedsQLTM 4.0 Generic Core Scale and PedsQLTM 3.0 Cancer Module. Results: The results showed that there were significant differences in quality of life between the generic and cancer module before and after the educational intervention in the elderly (p value = 0.012; 0.000). Conclusions: Parent’s education about leukemia, chemotherapy, and management of side effects can improve quality of life of children acute lymphocytic leukemia both generic and cancer module.